Characterization of large tilt-angle flexoelectro-optic switching in chiral nematic liquid crystal devices. Issue 3 (19th February 2019) - Wang, Xiuze; Fells, Julian A. J.; Welch, Chris; Tamba, Maria-Gabriela; Mehl, Georg H.; Morris, Stephen M.; Elston, Steve J.
ABSTRACT: The 'flexoelastic ratio' is commonly used to characterise the electro-optic behaviour of chiral nematic liquid crystal (LC) devices that exhibit flexoelectro-optic switching. There has been renewed interest in this electro-optic effect of late as new LC materials and mixtures have been developed that exhibit large tilt angles, Ø, of the optic axis (Ø ≥ 45°) whilst maintaining a fast response time (< 1 ms). In this study, we compare the different flexoelastic ratios that are obtained for fixed and variable-pitch chiral nematic LCs for materials with a tilt of the optic axis as large as Ø = ± 45°. We show that for large tilt angles of the optic axis the values for the two different flexoelastic ratios measurably diverge. Of the two ratios, we propose that for large tilt-angle mixtures it is more appropriate to use the flexoelastic ratio that is derived for the case when the pitch of the helix is constrained. In addition, a simple way of determining the 'pitch-constrained' flexoelastic ratio is presented that involves identifying the electric field amplitude at the point for which the transmission levels are the same for both positive and negative electric field polarities. GRAPHICAL ABSTRACT: